2009
DOI: 10.1088/1748-9326/4/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of greenness on the Yamal Peninsula, Russia: interactions of ecological and social factors affecting the Arctic normalized difference vegetation index

Abstract: The causes of a greening trend detected in the Arctic using the normalized difference vegetation index (NDVI) are still poorly understood. Changes in NDVI are a result of multiple ecological and social factors that affect tundra net primary productivity. Here we use a 25 year time series of AVHRR-derived NDVI data (AVHRR: advanced very high resolution radiometer), climate analysis, a global geographic information database and ground-based studies to examine the spatial and temporal patterns of vegetation green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 48 publications
7
76
0
Order By: Relevance
“…The development has left significant footprints on the vegetation cover. These footprints were found not only at the development sites but also across large distances (Walker et al, 2009;Kumpula et al, 2012). More specifically, Kumpula et al (2011) reported extensive transformation from shrub-to more productive (greener) grass-and sedge-dominated tundra in NWS that reclaim artificial terrain disturbances at Bovanenkovskiy gas field, Yamal peninsula (70 • N).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The development has left significant footprints on the vegetation cover. These footprints were found not only at the development sites but also across large distances (Walker et al, 2009;Kumpula et al, 2012). More specifically, Kumpula et al (2011) reported extensive transformation from shrub-to more productive (greener) grass-and sedge-dominated tundra in NWS that reclaim artificial terrain disturbances at Bovanenkovskiy gas field, Yamal peninsula (70 • N).…”
Section: Introductionmentioning
confidence: 90%
“…For example, for the Yamal peninsula, Elsakov and Teljatnikov (2013) concluded that its widely referred greening (Macias-Fauria et al, 2012) could be traced to statistically significant changes over just 4.8 % of the total area. Moreover, this greening was linked to shrub growth on the patches with disturbed permafrost or within the patches of already established shrubs (Walker et al, 2009). Barichivich et al (2014) noted that browning in southern forest biomes could also be partially associated with disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most tundra vegetation is summer-temperature limited so summer warming will generally enhance productivity, however, other local factors are also important such as glacial history [22], winter temperatures, snow cover, precipitation, soil moisture [23], and land-use history [24,25]. These factors are very important for understanding the very heterogeneous signals that are coming from global assessments of plot-scale response to experimental warming [23].…”
Section: Background and Rationalementioning
confidence: 99%
“…Jia et al 2009;Walker et al 2009). A variety of tundra manipulative experiments and observations suggest vegetation productivity is increasing with rising temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%